The effect of different drying methods on the chemical constituents of rubus rosifolius (Sampinit) fruit in the Philippines - Chiu, Hennie Hillary C. (Animo Repository, 2023)
Rubus rosifolius is an underutilized fruit found in the provinces of Laguna and Quezon which can offer economic importance as it can be developed in a multitude of ways as well as potential health benefits to humans. Thus, this research aimed to determine the effect of different drying methods on the phenolic content, total tannin concentration, antioxidative properties, flavonoid content, and compounds present in the methanolic extract of fresh samples. The phenolic content, tannin concentration, antioxidant properties, and flavonoid content are measured through spectroscopic techniques, while the compounds in methanolic extract are determined using Gas Chromatography-Mass Spectroscopy. The results showed that dehydrating using an electric food-grade dehydrator can maintain total tannin concentration and minimize loss of phenolic content in fresh samples. Freeze-dried extracts showed the highest antioxidant capacity, while air-dried extracts can minimize loss of flavonoid content in fresh R. rosifolius samples. Finally, the dehydrated extracts showed the presence of the compounds hydroxymethyl-furfural and, 4-dihydroxy-2,5-dimethyl-3(2H)-furan-3-one which are found in Rubus species. Keywords: Rubus rosifolius, metabolomics, polyphenols, drying, dehydrated, freeze dry